The positive education of challenge: innovative integration of challenge based learning and positive education - Horikoshi, Keisuke (Frontiers in Psychology, 2023)
Challenge based learning is not generally considered part of positive education. This study argues that challenge based learning should be considered and integrated with positive education to advance it from three perspectives. First, the aims of both educational approaches emphasize the promotion of engagement, meaning, achievement, and learning. Second, empirical studies suggest that challenge based learning is likely to enhance well-being and learning outcomes, aligning with positive education's impact. Third, incorporating challenge based learning in positive education will likely address multiple criticisms of positive education and help advance it by incorporating real-life challenges, meaningful contexts, experiential learning, collective perspectives, and educational studies. To advance positive education, more empirical studies should be conducted on the impact of challenge based learning on well-being to fill the research gap in quantity, scope of variables, and longitudinal studies, with due consideration of its variety in implementation. Furthermore, innovative integration of challenge based learning and existing positive education interventions should be explored based on comparative analyses of both approaches to develop positive education that enables learners to flourish with challenges at the individual and collective levels. Positive education that explicitly incorporates challenges is called the positive education of challenge. To advance the positive education of challenge, more educational approaches (other than challenge based learning) that focus on challenges (e.g., challenge courses and pedagogy of challenge) should also be explored for integration with positive education.